Takaful made simple: for students and young professionals - Che Mohd Salleh, Marhanum; Abdullah, Nurdianawati Irwani (Kulliyyah of Economics and Management Sciences, IIUM, 2025)
Takaful provides more than financial protection, it upholding the ethical and spiritual values central to a responsible and compassionate society. Unlike conventional insurance, Takaful is built on mutual cooperation, shared responsibility, and solidarity, ensuring that individuals support one another in times of hardship rather than simply transferring risk for profit. It encourages disciplined financial planning, safeguards families and businesses against unexpected losses, and ensures that all contributions are invested in halal and socially responsible ways. By combining practical risk management with Islamic principles such as fairness, mutual help, and community well-being, Takaful becomes more than a financial product, it becomes a system that nurtures trust, strengthens social bonds, and promotes collective resilience in everyday life.